Whole exome sequencing identifies rare biallelic ALMS1 missense and stop gain mutations in familial Alström syndrome patients - Kamal, Naglaa M. (Saudi J Biol Sci, 2020)
Alström syndrome (AS, OMIM ID 203800) is a rare childhood multiorgan disorder, which is widely studied in non-Arab ethnic patients. The clinical and molecular basis of AS and the mode of disease inheritance in consanguineous Arab populations is not well investigated. Therefore, to identify the molecular basis of AS in familial forms, the present study performed whole exome sequencing of 5 AS patients belonging to 2 different Bedouin families from Saudi Arabia. The present study identified the AS causative rare biallelic mutations in ALMS gene:T376S in exon 5 and S909* in exon 8 for family A and an R2721* in exon 10 (R2721*) for family B. ALMS1 targeted genetic sequencing of healthy population controls and family members has confirmed its extremely rare frequency and autosomal recessive mode of inheritance. The truncating mutations S909* and R2721* could cause the loss of CC domains and ALMS motif on C-terminal end of the protein and creates unstable protein, which eventually undergoes intracellular degradation. The premature protein truncating mutations described in our study may eventually provide further insight into the functional domains of the ALMS1 protein and contribute to the understanding of the phenotypic spectrum of AS. Whole exome sequencing based molecular diagnosis is expected to rule out ambiguity surrounding clinical diagnosis of suspected AS cases.